KATEKESE PENDALAMAN KITAB SUCI UNTUK MENINGKATKAN RASA PERCAYA DIRI DAN KEBERANIAN MENGUNGKAPKAN PENGALAMAN IMAN BAGI ANAK BINAAN EMAUS DALAM RANGKA BULAN KITAB SUCI NASIONAL TAHUN 2020 - Ason Ason; Septian Peterianus (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Melawi, 2021)
Abstract: The purpose of this service activity is to introduce the holy book as a source of faith and inspiration for life. Specifically, the aim of this activity is to increase the confidence and courage of the boarders who are assisted by Emmaus in sharing their faith experiences based on the scriptures. The method used in deepening the scriptures is the catechetical method of the people. In-depth meetings are held 1 (once) a week for 4 (four) weeks in September 2020. Each meeting has a sub-theme as an elaboration of the big theme, namely: